Bioadsorption of Copper(II) Using Halmahera Specific Marine Algae (Sargassum turbinarioides) Encapsulated Calcium Alginate - Sanawi, Dede Ardiansyah Takdir Abubakar; Rumhayati, Barlah; Fardiyah, Qonitah (Universitas Gadjah Mada, 2025)
This study investigated the conditions for bioadsorption of copper(II) using Halmahera marine algae (Sargassum turbinarioides) encapsulated with calcium alginate by batch method. Physicochemical parameters of biosorption, including contact time, biosorbent mass, pH, and copper(II) concentration, were studied to determine the percentage of copper(II) adsorbed. The maximum percentage of copper(II) bioadsorption was 96.4% under the optimum bioadsorption conditions with a contact time of 90 min, a biosorbent mass of 2 g, a solution pH of 5, and a copper(II) concentration of 60 mg/L. The bioadsorption isotherm study showed that the Langmuir model is more suitable for modeling copper(II) bioadsorption, while the bioadsorption kinetics study showed a pseudo-second-order kinetic model. Characterization of the biosorbent using FTIR showed that the biosorbent has active functional groups such as O–H, C–H, S–H, C=O, S=O, and C–O–C, which act as metal ligands, and SEM characterization showed morphological changes in the biosorbent before and after the copper(II) bioadsorption process.